An Employment of Restorative Justice Procedure in Mediation of an Investigation Unit at Si-Thep Provincial Police Station, Phetchabun Province - Senwong, Nutthaphon; Rattanasermpong, Mayuree; Subruangthong, Waraporn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This study aims to: 1. examine the current practices and challenges in the mediation processes of the investigation unit, and 2. propose guidelines for integrating restorative justice principles into mediation practices within the investigation unit of Sri Thep Police Station, Sri Thep District, Phetchabun Province. This qualitative research utilized in-depth interviews with 10 purposively selected participants. The research instrument was a semi-structured interview comprising 11 questions, and the data were analyzed using descriptive content analysis. The findings revealed that: 1. Mediation in the investigation unit of Sri Thep Police Station typically occurs following a formal complaint. The process involves three stages: 1) pre-mediation, 2) during mediation, and 3) post-mediation. 2 The guidelines for incorporating restorative justice principles into mediation include: 1) fostering mutual understanding and listening to the needs of the disputing parties, 2) organizing training sessions to enhance mediation skills for investigators, and 3) providing accessible and suitable venues for mediation sessions.